The incredible life of Balto - McCarthy, Meghan (New York : Knopf, 2011)
Illustrations and text describe the life of Balto, the real-life, legendary sled dog that braved a deadly blizzard to bring a lifesaving serum to people in Alaska in 1925, focusing on the dog's life after his celebrity-status waned.
Map on endpapers.
Includes bibliographical references.
Booklist
Publisher's Weekly
School Library Journal
Booklist, July 2011
Keywords: Balto (Dog) -- Juvenile literature; Diphtheria -- Alaska -- Nome -- Juvenile literature; Sled dogs -- Alaska -- Juvenile literature; Balto (Dog); Diphtheria -- Alaska -- Nome; Sled dogs -- Alaska; Balto (Dog); Diphtheria; Sled dogs; Picture books for children